Plasma Metabolome Signature Indicative of BRCA1 Germline Status Independent of Cancer Incidence - Penkert, Judith; Märtens, Andre; Seifert, Martin; Auber, Bernd; Derlin, Katja; Hille-Betz, Ursula; Hörmann, Philipp; Klopp, Norman; Prokein, Jana; Schlicker, Lisa; Wacker, Frank; Wallaschek, Hannah; et al. (Frontiers in Oncology, 2021)
Individuals carrying a pathogenic germline variant in the breast cancer predisposition gene BRCA1 (gBRCA1+) are prone to developing breast cancer. Apart from its well-known role in DNA repair, BRCA1 has been shown to powerfully impact cellular metabolism. While, in general, metabolic reprogramming was named a hallmark of cancer, disrupted metabolism has also been suggested to drive cancer cell evolution and malignant transformation by critically altering microenvironmental tissue integrity. Systemic metabolic effects induced by germline variants in cancer predisposition genes have been demonstrated before. Whether or not systemic metabolic alterations exist in gBRCA1+ individuals independent of cancer incidence has not been investigated yet. We therefore profiled the plasma metabolome of 72 gBRCA1+ women and 72 age-matched female controls, none of whom (carriers and non-carriers) had a prior cancer diagnosis and all of whom were cancer-free during the follow-up period. We detected one single metabolite, pyruvate, and two metabolite ratios involving pyruvate, lactate, and a metabolite of yet unknown structure, significantly altered between the two cohorts. A machine learning signature of metabolite ratios was able to correctly distinguish between gBRCA1+ and controls in ~82%. The results of this study point to innate systemic metabolic differences in gBRCA1+ women independent of cancer incidence and raise the question as to whether or not constitutional alterations in energy metabolism may be involved in the etiology of BRCA1-associated breast cancer.